2013
DOI: 10.1186/bcr3587
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Progesterone receptor assembly of a transcriptional complex along with activator protein 1, signal transducer and activator of transcription 3 and ErbB-2 governs breast cancer growth and predicts response to endocrine therapy

Abstract: Introduction: The role of the progesterone receptor (PR) in breast cancer remains a major clinical challenge. Although PR induces mammary tumor growth, its presence in breast tumors is a marker of good prognosis. We investigated coordinated PR rapid and nonclassical transcriptional effects governing breast cancer growth and endocrine therapy resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 76 publications
(156 reference statements)
1
26
0
Order By: Relevance
“…Numerous findings strongly demonstrated that fulllength ErbB-2 is present in the nucleus of BC cells, where it binds promoters/enhancers of target genes to regulate biological responses in BC (Tan et al 2002, Wang et al 2004, Kim et al 2009, Beguelin et al 2010, Li et al 2011, Diaz Flaque et al 2013a,b, Cordo Russo et al 2015. Importantly, the development of more sophisticated techniques to study protein trafficking from the cytoplasmic membrane to different subcellular compartments, allowed further understanding of the mechanism involved in ErbB-2 nuclear translocation.…”
Section: Nuclear Erbb-2 Action In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous findings strongly demonstrated that fulllength ErbB-2 is present in the nucleus of BC cells, where it binds promoters/enhancers of target genes to regulate biological responses in BC (Tan et al 2002, Wang et al 2004, Kim et al 2009, Beguelin et al 2010, Li et al 2011, Diaz Flaque et al 2013a,b, Cordo Russo et al 2015. Importantly, the development of more sophisticated techniques to study protein trafficking from the cytoplasmic membrane to different subcellular compartments, allowed further understanding of the mechanism involved in ErbB-2 nuclear translocation.…”
Section: Nuclear Erbb-2 Action In Breast Cancermentioning
confidence: 99%
“…Also, providing consistent correlation between ErbB-2's role as a coactivator and its ability to promote BC growth, another study demonstrated that progestins induce the assembly of a transcriptional complex among activator protein 1 (AP-1), Stat3, PR and ErbB-2 at a region of the cyclin D1 promoter containing both AP-1 response elements (TRE) and GAS sites (Diaz Flaque et al 2013a). This array of transcription factors (AP-1 and Stat3) whose response elements are clustered in the DNA, plus their interacting cofactors (PR and ErbB-2) and coactivators (P300 and CBP), function cooperatively to induce cyclin D1 promoter activation as well as in vitro and in vivo BC growth driven by progestins (Diaz Flaque et al 2013a).…”
Section: :12mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, 43% of PNETs overexpressed CCND1, which tended to be associated with advanced clinical stage [18] . CCND1 promoter was reported to be stimulated by a large number of transcription factors, mostly c-Fos and c-Jun [16,17] . Activation of CCND1 through progestin has previously been reported in breast cancer [16] , although CCND1 lacks the progesterone response element [19] .…”
mentioning
confidence: 99%
“…Cyclin D1 (CCND1), which regulates the proliferation of cells via the restriction point during the late G1 phase [15] , was reported to be overexpressed in various malignancies [16,17] . For instance, 43% of PNETs overexpressed CCND1, which tended to be associated with advanced clinical stage [18] .…”
mentioning
confidence: 99%